Indigenous Policy Knowledge in Thematic Forest Governance of Yogyakarta - Ameylia Puspita Rosa Dyah Ayu Arintyas; Kuncoro Cahyo Aji; Rima Maryani (Journal of Indonesian Rural and Regional Government, 2026)
The thematic forest governance initiative in Yogyakarta is a pioneering case study in integrating indigenous knowledge into modern environmental management. This approach moves beyond traditional, top-down models towards a more participatory and adaptive framework. The initiative is deeply rooted in the Javanese philosophical concept of Memayu Hayuning Bawana, which emphasizes the ethical responsibility of humans to maintain cosmic and ecological harmony. This philosophy is tangibly demonstrated through the concept of resan or rekso (guardian), where local communities act as protectors of their environment by conserving water sources and protecting specific trees. The model, which blends indigenous values with formal policy instruments, is evident in the creation of thematic forest categories like Wana Boga, which links forest conservation to local food systems and supports household economies. The success of this governance model relies on a collaborative, multi-actor approach involving the Governor, the Yogyakarta Environmental and Forestry Service (DLHK DIY), and Forest Farmer Groups (KTH). While the initiative offers a promising pathway for sustainable and equitable resource management, it still faces challenges such as the risk of commodifying traditional practices and potential power imbalances. Nevertheless, the thematic forest program highlights the capacity of indigenous perspectives to enrich governance and contribute to more sustainable, resilient, and culturally grounded futures, aligning with international goals for poverty reduction, food security, and biodiversity conservation.